Variation in the D-loop of Arctic Charr (Salvelinus alpinus) morphs from Lake Thingvallavatn - Escudero, Javier Negueruela (2011)
There are four morphs of arctic charr (Salvelinus alpinus) present in post-glacial formed Lake Thingvallavatn. The morphs can be classified according to phenotypical and ecotypical differences: small benthivorous, large benthivorous, planktivorous and piscivorous. Because of the morphological differences some genetical differences are expected that may explain the ecotypes. To check for genetical differences I studied the D-loop, a mithocondrial DNA region, in 264 individuals of arctic charr, focusing in the differences between the small benthics versus the planktivorous and having as reference the large benthics. The results show that the morphological differences between the morphs doesn’t correlate with the D-loop genotype by the genetics didn’t appear because of the morphs, there is however weak genetic differentiation between sexes. The study of the developmental gene FGOP2 in 54 individuals does not indicate differences in allele frecuency between the three morph types in Lake Thingvallavatn.